Philosophy and the Jewish tradition : lectures and essays - Motzkin, Aryeh Leo, 1934-2006 (Studies in Jewish history and culture, 2012)
Aryeh Motzin's extraordinary essays on the encounter between Jewish tradition and philosophy are collected in this volume. Motzkin examines how medieval Jewish thinkers understood Plato and Aristotle, and how these medieval thinkers were, in turn, understood by modern Jewish thinkers.